The Variations of Che Ju Do Korean Life Styles in Tokyo, Japan - Kim, Il Su (My University, 1985)
This dissertation is an exploratory study of life style variations among Koreans in Tokyo, Japan. The sample of Koreans, whose cultural origin is Che Ju Do, an island located off the southwest coast of South Korea, is classified into three groups: the first-generation which migrated to Japan prior to the end of World War II; the second-generation whose members were all born in Tokyo as offspring of the first group; and the recent migrant group which migrated to Japan since the end of World War II. While the first-generation and the recent migrant groups show similar life styles regardless of their age difference, the second-generation group shows life styles markedly different from the first two groups and discloses a wider variation of life styles within the group than within each of the other two groups. The milieu experienced by Koreans in Japan is bicultural, affecting each of the three groups differently. The first-generation and the recent migrant groups show stable life styles. The Korean cultural referent is a symbol in terms of which they articulate the Korean locus of interpretation and personal and ego identities. Concurrently, Koreans of these groups develop a conceptual and emotional separation from the Japanese domain. As a result, they are unlikely to experience marginality. The same milieu, however, is a constant source of personal trouble for the second-generation group. This is largely due to their ill-defined identification with either the Japanese or the Korean domain. Adopting Korean or Japanese identity and the Korean locus or the Japanese locus of interpretation becomes a serious personal issue. Hence, this group is likely to experience marginality. The theme of this dissertation concerns individuals' subjective interpretations of their sociocultural situations as expressed in the variety of life styles and in the strategies used to maintain them. The theoretical assumptions explain the development and maintenance of the relationships among culture, society, and individuals in terms of the following concepts: life style, ethnic identity, locus of interpretation, passing, marginality, and the bicultural milieu. How these concepts and their properties are inter-connected with particular sociocultural, historical, and politicoeconomic conditions reveal the differences and similarities of the life styles of these three groups.
Keywords: Anthropology; Anthropology